Atomic spectrometry update – a review of advances in environmental analysis. Issue 1 (21st November 2019) - Bacon, Jeffrey R.; Butler, Owen T.; Cairns, Warren R. L.; Cook, Jennifer M.; Davidson, Christine M.; Cavoura, Olga; Mertz-Kraus, Regina
Abstract : This review covers advances in the analysis of air, water, plants, soils and geological materials by a range of atomic spectrometric techniques including atomic emission, absorption, fluorescence and mass spectrometry. Abstract : In the field of air analysis, highlights within the period covered by this review included a wearable air sampler with an inbuilt GPS sensor which enabled autonomous sampling to be performed at specific sites once the device had been preprogrammed with the requisite location coordinates. A prototype high resolution laser absorption spectroscopic instrument was developed as a potential SI-traceable alternative to ID-CV-ICP-MS for determining mercury concentrations in air and its isotopic composition. Improvements in the capabilities of single-particle aerosol mass spectrometers were noted. New measurements using tools such as LDI-MS and PTR-MS are providing new insights into the composition of carbonaceous particles. A large amount of effort continues to be directed towards multi-element preconcentration methods for water analysis, using either liquid or solid phase extraction to boost the sensitivity of instrumentation. Species-specific preconcentration methods were developed for the determination of mercury or arsenic species and methodologies employed to isolate elements from matrices such as seawater before isotope-ratio determinations. The focus of elemental speciation has shifted towards elemental fractionation with the determination of nano-sized fractions. The advent of ICP-MS/MS instrumentation has made the analysis of non-metallic elements such as F or P possible with improved detection limits. An interesting development of the isotope dilution technique was the use of isotopically labelled cell gasses to investigate the possibility of carrying out isotope dilution analysis of monoisotopic elements such as As or Y. Much effort has been devoted to characterising new and existing matrix-matched reference materials for calibration and quality control in the determination of the elemental and isotopic composition of geological samples. Zircon geochronology is a very active area of research and there is now considerable interest in developing U–Pb dating methods for other accessory minerals and carbonates. The application of in situ techniques such as LA-ICP-MS, SIMS, and LIBS to obtain geochemical information at high spatial resolution is another continuing theme. The ongoing interest in the optimisation of methods for extraction of analytes from soil and plants included developments relating to nanoparticles, estimation of bioavailability and non-chromatographic speciation analysis. The relative maturity of the AAS, AES and AFS techniques means that there have been few reports of major advances in these fields. Many of the developments in ICP-MS have been driven by the increased availability of ICP-MS/MS instrumentation. The importance of sample preparation in LIBS has increasingly been recognised. Proximal analysis – in which chemometric approaches are applied to data obtained by atomic (and molecular) spectroscopy to infer physical or chemical properties of a sample e.g. the pH of a soil – are becoming more common, in particular in relation to field-portable techniques such as LIBS and pXRFS, with increased attention being paid to the opportunities arising from data fusion.